Local Bank Financial Constraints and Firm Access to External Finance - PARAVISINI, DANIEL (Journal of Finance, 2008)
ABSTRACT I exploit the exogenous component of a formula‐based allocation of government funds across banks in Argentina to test for financial constraints and underinvestment by local banks. Banks are found to expand lending by $0.66 in response to an additional dollar of external financing. Using novel data to measure risk and return on marginal lending, I show that the profitability of lending does not decline and total borrower debt increases during lending expansions, holding investment opportunities constant. Overall, financial shocks to constrained banks are found to have a quick, persistent, and amplified effect on the aggregate supply of credit.